2003
DOI: 10.1097/01.tp.0000084307.39680.7d
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced three-dimensional magnetic resonance angiography versus conventional digital subtraction angiography: which modality is superior in evaluating living kidney donors?1

Abstract: This study evaluates the correlation of magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) with the operative vessel findings in living kidney donors. The intraoperative vessel findings of 52 living renal donors were compared with the preoperative diagnoses of each imaging technique. Sixty-seven arteries were found during explantation. Forty kidneys showed a single arterial blood supply, and 12 kidneys showed a multiple arterial blood supply. No advantage of either imaging method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 10 publications
3
12
0
1
Order By: Relevance
“…Recently, minimally invasive laparoscopic donor nephrectomy has been introduced. In laparoscopic donor nephrectomy, grafts with early branching arteries, as seen in 6.5%-9.6% of the main renal arteries, 19,20 are likely to be MRA grafts because the length of the renal artery has been reduced by the use of vascular staplers. Oh et al 21 reported finding two or more renal arteries in 6 of 62 donors (9.7%), although preoperative imaging indicated only one renal artery, because of the staples fired across the vivisection of the main artery in laparoscopic nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, minimally invasive laparoscopic donor nephrectomy has been introduced. In laparoscopic donor nephrectomy, grafts with early branching arteries, as seen in 6.5%-9.6% of the main renal arteries, 19,20 are likely to be MRA grafts because the length of the renal artery has been reduced by the use of vascular staplers. Oh et al 21 reported finding two or more renal arteries in 6 of 62 donors (9.7%), although preoperative imaging indicated only one renal artery, because of the staples fired across the vivisection of the main artery in laparoscopic nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging role of magnetic resonance imaging angiography in pre-donation imaging, although recent studies have not demonstrated clear superiority of magnetic resonance imaging over CT angiography. [24][25][26] …”
Section: Urologic Considerations In Donor/kidney Selectionmentioning
confidence: 98%
“…In contrast to this, the reliability of MRA is not affected by impaired renal function or the presence of bilateral renovascular disease. 5,12,13 Moreover, it is unnecessary to hydrate the patients or to stop the use of diuretics before the examination. Another suggested advantage of MRA is the possibility of evaluating not only arterial but also venous vasculature.…”
Section: Mra In Comparison With Conventional Intra-arterial Angiographymentioning
confidence: 99%